Geothermal Fluid Variation Recorded by Banded Ca-Carbonate Veins in a Fault-Related, Fissure Ridge-Type Travertine Depositional System (Iano, southern Tuscany, Italy). (30th January 2021) - Matera, Paola Francesca; Ventruti, Gennaro; Zucchi, Martina; Brogi, Andrea; Capezzuoli, Enrico; Liotta, Domenico; Yu, Tsai-Luen; Shen, Chuan-Chou; Huntington, Katharine W.; Rinyu, László; Kele, Sándor
Abstract : Banded Ca-carbonate veins in travertine deposits are efficient recorders of the compositional fluctuations of geothermal fluids flowing (or flowed) from deep reservoirs up to the surface, within fault zones. In this view, these veins represent key tools for decoding those factors that influenced the geochemical variations. We have analyzed veins developed in fractures channeling geothermal fluids forming travertine deposits. The studied veins cut a fossil travertine fissure ridge, near the Larderello geothermal area (Iano area, southern Tuscany) where geothermal fluid circulation is favored by NE-trending strike-to-oblique-slip faults and their intersections with NW-trending normal ones. U-Th dating indicates that fluid circulation occurred from (at least) 172 ka to 21 ka. In this time span, the geothermal fluid changed in composition, and the banded Ca-carbonate veins recorded these variations in terms of mineralogical and stable isotope composition and temperature (T ) of deposition. We also documented for the first time the occurrence of Mn-rich black tree-shaped structures within the veins. Mineralogy coupled with stable and clumped isotope measurements allows the reconstruction of some features (i.e., crystal texture, temperature, and CO2 origin) and the inference of the processes (i.e., pH, T, and pCO2 variations) that have controlled the fluid evolution through time. Multiple-stage and one-stage deposition processes have played an important role in modifying the stable isotope composition of banded Ca-carbonate veins; temperature coupled with pCO2 also influenced their mineralogical composition. Interpreted in the context of the tectonic setting, the data show that the NW-trending faults have mainly controlled travertine deposition. Their intersection with NE-trending faults, interpreted as transfer faults, highlights the important role of transfer zones in channeling the geothermal fluids.